One year comparison of costs of coronary surgery versus percutaneous coronary intervention in the stent or surgery trial. Issue 7 (14th June 2004) - Weintraub, W S; Mahoney, E M; Zhang, Z; Chu, H; Hutton, J; Buxton, M; Booth, J; Nugara, F; Stables, R H; Dooley, P; Collinson, J; Stuteville, M; et al.
Abstract : Objectives: To compare initial and one year costs of coronary artery bypass grafting (CABG) versus percutaneous coronary intervention (PCI) in the stent or surgery trial. Design: Prospective, unblinded, randomised trial. Setting: Multicentre study. Patients: 988 patients with multivessel disease. Interventions: CABG and stent assisted PCI. Main outcome measures: Initial hospitalisation and one year follow up costs. Results: At one year mortality was 2.5% in the PCI arm and 0.8% in the CABG arm (p  =  0.05). There was no difference in the composite of death or Q wave myocardial infarction (6.9% for PCI v 8.1% for CABG, p  =  0.49). There were more repeat revascularisations with PCI (17.2% v 4.2% for CABG). There was no significant difference in utility between arms at six months or at one year. Quality adjusted life years were similar 0.6938 for PCI v 0.6954 for PCI, Δ  =  0.00154, 95% confidence interval (CI) −0.0242 to 0.0273). Initial length of stay was longer with CABG (12.2 v 5.4 days with PCI, p < 0.0001) and initial hospitalisation costs were higher (£7321 v £3884 for PCI, Δ  =  £3437, 95% CI £3040 to £3848). At one year the cost difference narrowed but costs remained higher for CABG (£8905 v £6296 for PCI, Δ  =  £2609, 95% CI £1769 to £3314). Conclusions: Over one year, CABG was more expensive and offered greater survival than PCI but little added benefit in terms of quality adjusted life years. The additional cost of CABG can be justified only if it offers continuing benefit at no further increase in cost relative to PCI over several years.